Use of Outpatient Care in Veterans Health Administration and Medicare among Veterans Receiving Primary Care in Community-Based and Hospital Outpatient Clinics - Liu, Chuan-Fen (Blackwell Science Inc, 2010)
OBJECTIVE: To examine differences in use of Veterans Health Administration (VA) and Medicare outpatient services by VA primary care patients. DATA SOURCES/STUDY SETTING: VA administrative and Medicare claims data from 2001 to 2004. STUDY DESIGN: Retrospective cohort study of outpatient service use by 8,964 community-based and 6,556 hospital-based VA primary care patients. PRINCIPAL FINDINGS: A significant proportion of VA patients used Medicare-reimbursed primary care (>30 percent) and specialty care (>60 percent), but not mental health care (3–4 percent). Community-based patients had 17 percent fewer VA primary care visits (p<.001), 9 percent more Medicare-reimbursed visits (p<.001), and 6 percent fewer total visits (p<.05) than hospital-based patients. Community-based patients had 22 percent fewer VA specialty care visits (p<.0001) and 21 percent more Medicare-reimbursed specialty care visits (p<.0001) than hospital-based patients, but no difference in total visits (p=.80). CONCLUSIONS: Medicare-eligible VA primary care patients followed over 4 consecutive years used significant primary care and specialty care outside of VA. Community-based patients offset decreased VA use with increased service use paid by Medicare, suggesting that increasing access to VA primary care via community clinics may fragment veteran care in unintended ways. Coordination of care between VA and non-VA providers and health care systems is essential to improve the quality and continuity of care.